Desain Pembelajaran Berbasis STEM pada Materi Pesawat Sederhana di Sekolah Dasar - Julya Fauziah; Syarip Hidayat; Agnestasia Ramadhani Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the limited research on STEM based learning design for simple machines in elementary schools. In fact, this topic holds great potential to be integrated into contextual and creative learning that meets 21st-century educational demands. The purpose of this research is to analyze current trends and describe a STEM based learning design for simple machines in elementary schools using the Project Based Learning (PjBL) model. The research method applied was a systematic literature review, examining relevant articles published between 2019 and 2025 concerning STEM education at the elementary level, with a focus on simple machines. The literature selection process included identification, screening, and content analysis, resulting in approximately 24 articles that met the inclusion criteria. The findings indicate that research on STEM in elementary schools is steadily increasing; however, most studies emphasize general scientific literacy, energy, and environmental issues, leaving research on simple machines relatively scarce. Further analysis highlights the strong potential of implementing STEM approaches in teaching simple machines through projects, experiments, and problem solving activities based on real life contexts. The proposed treatment in experimental classes can involve projects such as creating miniature simple machines like seesaws, pulleys, or inclined planes using materials from the school environment. Thus, this study emphasizes the importance of expanding STEM implementation in elementary schools to more contextual topics, thereby enhancing students critical thinking, collaboration, and problem solving skills.